Antibody Titers Against Human Cytomegalovirus gM/gN and gB Among Pregnant Women and Their Infants - Talavera-Barber, Maria; Flint, Kaitlyn; Graber, Brianna; Dhital, Ravi; Kaptsan, Irina; Medoro, Alexandra K.; Sánchez, Pablo J.; Shimamura, Masako (Frontiers in Pediatrics, 2022)
Congenital CMV (cCMV) infection can affect infants born to mothers with preconceptional seroimmunity. To prevent cCMV due to nonprimary maternal infection, vaccines eliciting responses exceeding natural immunity may be required. Anti-gM/gN antibodies have neutralizing capacity in-vitro and in animal models, but anti-gM/gN antibodies have not been characterized among seroimmune pregnant women. Paired maternal and infant cord sera from 92 CMV seropositive mothers and their full-term or preterm infants were tested for anti-gM/gN antibody titers in comparison with anti-gB titers and neutralizing activity. Anti-gM/gN titers were significantly lower than anti-gB titers for all groups and did not correlate with serum neutralizing capacity. Further study is needed to determine if higher anti-gM/gN antibody titers might enhance serum neutralizing capacity among seropositive adults.